Optimal instantaneous prediction of voltage instability due to transient faults in power networks taking into account the dynamic effect of generators. Issue 1 (31st December 2022) - Khalili, Mohsen; Ali Dashtaki, Mohammad; Nasab, Morteza Azimi; Reza Hanif, Hamid; Padmanaban, Sanjeevikumar; Khan, Baseem
Abstract: Changes in consumption and changes in the structure of the system always occur in each power system. One of the effects of these changes can be the instability of the system voltage. When voltage is unstable, their performance is in conditions of power fluctuations after large errors occur. Determining the voltage stability of traditional methods is time consuming and does not have the necessary efficiency for instantaneous monitoring. In this paper, an index based on the changes of two indices of frequency deviation and frequency response of inertia in the time after the occurrence of perturbation is presented, which has the ability to detect the occurrence of instability and at the same time high speed timely estimation of voltage instability in the power system. In addition, this indicator has been used to determine the appropriate time to start load removal (voltage reduction load). All simulations are performed on the IEEE 33-bus network in DIgSILENT software, the results of which indicate that the proposed index has a very low computational load. Because the proposed method for instantaneous voltage instability prediction does not depend on the network structure and load model and does not require any threshold value. Therefore, the proposed index has a very low computational load. These advantages make the proposed method an interesting option for online and practical applications.